Three new species and two new records of Helochares (Hydrobaticus) MacLeay, 1871 from China (Coleoptera: Hydrophilidae: Acidocerinae) - Dong, Xue; Bian, Dongju (Zootaxa, 2021)
Helochares (Hydrobaticus) MacLeay, 1871 is the largest subgenus of Helochares Mulsant, 1844. The Chinese fauna of Helochares (Hydrobaticus) is still poorly known. Five species are recognized, including three herein described as new: Helochares (Hydrobaticus) hainanensis sp. n. (Hainan); H. wuzhifengensis sp. n. (Jiangxi); H. tengchongensis sp. n. (Yunnan). Helochares minor d’Orchymont, 1925 and H. nipponicus Hebauer, 1995 are recorded from China for the first time. Descriptions, diagnoses, and illustrations of the new species are given. Habitus and aedeagus photos of the new record species are provided.